Avaliação de moagem em circuito aberto e com peneira de alta frequência para minério de magnesita - Matheus Naves Moraes (2017)
The magnesite ores processing operation in Brumado needs to increase its production tonnage by 20% and the comminution stage was identified as the process main bottleneck. Currently, the process has four ball mills in closed circuit with hydrocyclones, preparing the ore to magnesites reverse flotation. Initially, this process was modeled in order to verify the grinding efficiency and define the initial parameters for the tests. To reduce the investment necessary to increase productivity, an innovative grinding concept was studied, combining open circuit and high frequency screener. Considering this configuration, it could be expected reductions of overgrinding and comminution specific energy. In addition, more homogeneous particle size distribution could be fed to flotation, which may increase selectivity and, hence, recovery. According to this concept, the proposed flowsheet divides the comminution in a primary grinding, open circuit with selective parameters, followed by classification on a high frequency screener. The screener undersize proceeds to desliming and flotation. The oversize, in turn, has to be directed to the secondary milling, preparing the ore to feed the flotation. In order to verify the parameters and model the process, pilot plant tests were carried out, evaluating the primary milling, classification and secondary milling. Furthermore, it was necessary to check the desliming and flotation, verifying the impact of the grinding modification in these processes. With the obtained results in the pilot plant trials, the milling was modeled and scaled up for the industrial process. As a consequence, the milling capacity could be increased by 11%. Moreover, as a result of the milling and classification efficiency improvement, the overmilling could be reduced, increasing the recovery. This fact, added to the better defined flow characteristics, as mineralogy and particle size, led to reduction in the losses from desliming and flotation, raising the mass recovery from 81.2 to 87.6%. These results project a 27% increase in the circuit production, thus surpassing the project objectives (20%). To conclude, the desliming, flotation, thickening and filtration processes were evaluated to identify new process bottlenecks. After the analyses, only flotation and filtration require interventions. For flotation, one additional bench will be necessary in both circuits. On the other hand, the filtration needs to be analyzed by a specialized company, since the current equipment already has restrictions